100 things to be when you grow up - Gerry, Lisa (Washington, D.C. : National Geographic Kids, 2017)
"From beekeeper to ice-cream taster, Chief Happiness Officer to Hollywood animal trainer, this book features 100 of the coolest, wackiest, and most amazing jobs out there (and some you never knew existed)! Jam-packed with inspiration, advice from National Geographic explorers, weird-but-true facts, and a heaping sense of wonder, this book will get kids excited about their future and all the amazing possibilities as they prepare to take on the world!"--Back cover.
Includes index.
Keywords: Vocational guidance -- Juvenile literature; Occupations -- Juvenile literature; Vocational guidance; Occupations; Professions -- Ouvrages pour la jeunesse; JUVENILE NONFICTION -- Body, Mind & Spirit; JUVENILE NONFICTION -- Curiosities & Wonders; Occupations; Vocational guidance; Vocational guidance; Occupations; Children's nonfiction; Literature; Juvenile works; Literature